2018
DOI: 10.21037/jss.2018.06.07
|View full text |Cite
|
Sign up to set email alerts
|

The impact of urgent intervention on the neurologic recovery in patients with thoracolumbar fractures

Abstract: Urgent surgery was associated with neurologic improvement in patients with spinal cord injury (SCI). This improvement was mainly observed in patients with an incomplete lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Not only could the disruption of the segmental vessels be a tool for clinicians for their initial neurological assessment, but it also may be a prognosis factor for potential recovery post-injury. There still needs to be precise data about the benefits of emergent surgical decompression, compared to delayed surgery, for patients with complete SCI [28]. However, our study suggests the segmental arteries could be wedged into or compressed by the fracture, so the acute distraction of the fracture, to remove the extrinsic compression is a theory that deserves further investigation.…”
Section: Discussionmentioning
confidence: 80%
“…Not only could the disruption of the segmental vessels be a tool for clinicians for their initial neurological assessment, but it also may be a prognosis factor for potential recovery post-injury. There still needs to be precise data about the benefits of emergent surgical decompression, compared to delayed surgery, for patients with complete SCI [28]. However, our study suggests the segmental arteries could be wedged into or compressed by the fracture, so the acute distraction of the fracture, to remove the extrinsic compression is a theory that deserves further investigation.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, we observed that early surgery did not decrease the rate of complications but did significantly decrease the duration of hospitalization. The findings on complications should be interpreted cautiously, as the rate of operative complications is closely associated with the injured segment, the skilfulness of the surgeon, and the technologies at the time of surgery, especially in studies from more than 5 years ago 15–20…”
Section: Discussionmentioning
confidence: 99%
“…The findings on complications should be interpreted cautiously, as the rate of operative complications is closely associated with the injured segment, the skilfulness of the surgeon, and the technologies at the time of surgery, especially in studies from more than 5 years ago. [15][16][17][18][19][20]…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…41,[45][46][47][48][49][50] Most studies on neurological outcome include patients with both complete and incomplete thoracic and thoracolumbar tSCI (Table 3). 13,16,41,51,52 Two studies evaluated the effect of surgical timing in thoracic tSCI specifically. 52,53 One study in 12 complete thoracic tSCI patients evaluated the efficacy of surgery.…”
Section: Impact Of Timing Of Surgical Interventionmentioning
confidence: 99%